2023
DOI: 10.1021/acs.molpharmaceut.2c00816
|View full text |Cite
|
Sign up to set email alerts
|

Sublimation of Drugs from the Site of Application of Topical Products

Abstract: The objective of the project was to investigate the plausibility of active pharmaceutical ingredients (APIs) to undergo sublimation from topical application following evaporation of solvent. Topical formulations with different APIs were subjected to a sublimation screening test. The APIs in the selected topical products were found to undergo sublimation to a different extent. The salicylic acid topical product was found to undergo a significant loss due to sublimation. The extent of sublimation of salicylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Therefore, the DF–NIC cocrystal can prevent the sublimation of neat DF during manufacturing and storage and increase its long-term stability, thus making the drug development economic and sustainable. There are other drugs also which are prone to loss due to sublimation, like salicylic acid, in which there is significant loss from the site of application . However, cocrystals have been prepared to prevent the loss due to sublimation by shielding the API …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the DF–NIC cocrystal can prevent the sublimation of neat DF during manufacturing and storage and increase its long-term stability, thus making the drug development economic and sustainable. There are other drugs also which are prone to loss due to sublimation, like salicylic acid, in which there is significant loss from the site of application . However, cocrystals have been prepared to prevent the loss due to sublimation by shielding the API …”
Section: Resultsmentioning
confidence: 99%
“…There are other drugs also which are prone to loss due to sublimation, like salicylic acid, in which there is significant loss from the site of application. 35 However, cocrystals have been prepared to prevent the loss due to sublimation by shielding the API. 36 Effect of Cocrystallization on the Dissolution Profile.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25,26 A recent study by Murthy and coworkers demonstrated that SA suffers significant weight loss at skin temperature (32 °C) by sublimation due to its high vapor pressure from its crystalline state as well as topical formulations. 27 The physical stability issues related to the high vapor pressure of APIs have been addressed by cocrystal/ salt formation or complexation with CDs. 28−32 Herein, we investigated the sublimation suppression of SA from the three polymorphic forms of the SA/(PEG/γ-CD-PPRX) complex, which were prepared by the previously reported sealed-heating technique.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, salicylic acid (SA) was selected as the model drug. SA is typically used in topical formulations to treat chronic skin diseases for its keratolytic, anti-inflammatory, and bacteriostatic properties. , A recent study by Murthy and co-workers demonstrated that SA suffers significant weight loss at skin temperature (32 °C) by sublimation due to its high vapor pressure from its crystalline state as well as topical formulations . The physical stability issues related to the high vapor pressure of APIs have been addressed by cocrystal/salt formation or complexation with CDs. Herein, we investigated the sublimation suppression of SA from the three polymorphic forms of the SA/(PEG/γ-CD-PPRX) complex, which were prepared by the previously reported sealed-heating technique. , The sublimation rate of SA was determined by thermogravimetry under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%